Prevalence of early onset neonatal septicemia in babies born to mother with pre-eclampsia - Dr. Dipak Madavi; Dr. Bhagyashree Tirpude; Dr. Santosh Daberao (Pediatric Review: International Journal of Pediatric Research, 2019)
Context: Pregnancy induced hypertension (PIH) is one of the important risk factor for preterm delivery. Neutropenia and thrombocytopenia are well recognized neonatal sequelae to maternal hypertension in pregnancy. Preeclampsia-associated neutropenia is a risk factor for an increased incidence of infection in preterm neonates. Methods & material: 87 neonates born to mother with preeclampsia were included with aim to find prevalence of EOS and their haematological profile. Diagnostic work up includes complete blood count, CRP, blood culture and sensitivity (C/S) and other relevant investigations according to cases. Result: Out of 87 neonates, 7 neonates had EOS (8%) with blood culture proven bacterial sepsis, Klebsiella pneumonia (57.14%) was commonest organism isolated followed by E. Coli (28.57%) and Enterococci (14.28%). About 32 (36.76%) mothers had severe hypertension and 55(68.22%) mothers had mild to moderate preeclampsia. About 60(68.79%) neonates were born preterm. 40 (45%) neonates had neutropenia. 38 (43.65%) babies had thrombo-cytopenia. All 7 septic babies had neutropenia and thrombocytopenia. Conclusion: Early onset septicemia is more common in babies born to mother with preeclampsia due to associated Prematurity, Neutropenia and Thrombocytopenia. Hence preventive measures should focus on recognition of these high risk neonates with prompt laboratory screening for sepsis and early institution of empirical antibiotics based on local data.